Pseudomembranous colitis due to Clostridium difficile as a cause of perineal necrotising fasciitis. (22nd January 2013) - Duburcq, Thibault; Parmentier-Decrucq, Erika; Poissy, Julien; Mathieu, Daniel
Abstract : Although rare, pseudomembranous colitis may be a cause of perineal necrotising fasciitis in a context of immunosuppression, as in the case we report. This origin must be quickly identified because the therapeutic management, especially surgery, is unlikely to be the same as usual. Similarly, antibiotic treatment is also a matter of discussion due to the potential deleterious role of antibiotics in pseudomembranous colitis.